(untitled) (The Pakistan Development Review, 1998)
Domestic poverty and income distribution are closely related to the state of the economy, which is linked with internal and external economic policies. Since 1988, under the rubric of structural adjustment programme (SAP), Pakistan has made use of fiscal, monetary and trade policies to correct her macro economic imbalances. It is hard to substantiate with proof that these programmes protect the poor. A number of studies have found that income distribution has been getting worse during the adjustment period in Pakistan.1 For example, Kemal (1994); Jaffery and Khattak (1995) and Anwar (1996) found that SAP accompanied with rising income inequality and poverty in Pakistan. But these studies are restricted as they did not employ an adequate methodology to assess the impact of structural adjustment reforms on income distribution.2 This paper, however, uses a simple static fixed-price SAM-based framework to analyse distributional outcome of incomes for rural and urban households. This methodology is useful because social accounting matrix (SAM) represents the whole economy and it does not need a large data set.